A cluster randomised controlled trial of advice, exercise or multifactorial assessment to prevent falls and fractures in community-dwelling older adults: protocol for the prevention of falls injury trial (PreFIT). Issue 1 (18th January 2016) - Bruce, Julie; Lall, Ranjit; Withers, Emma J; Finnegan, Susanne; Underwood, Martin; Hulme, Claire; Sheridan, Ray; Skelton, Dawn A; Martin, Finbarr; Lamb, Sarah E
Abstract : Introduction: Falls are the leading cause of accident-related mortality in older adults. Injurious falls are associated with functional decline, disability, healthcare utilisation and significant National Health Service (NHS)-related costs. The evidence base for multifactorial or exercise interventions reducing fractures in the general population is weak. This protocol describes a large-scale UK trial investigating the clinical and cost-effectiveness of alternative falls prevention interventions targeted at community dwelling older adults. Methods and analysis: A three-arm, pragmatic, cluster randomised controlled trial, conducted within primary care in England, UK. Sixty-three general practices will be randomised to deliver one of three falls prevention interventions: (1) advice only; (2) advice with exercise; or (3) advice with multifactorial falls prevention (MFFP). We aim to recruit over 9000 community-dwelling adults aged 70 and above. Practices randomised to deliver advice will mail out advice booklets. Practices randomised to deliver 'active' interventions, either exercise or MFFP, send all trial participants the advice booklet and a screening survey to identify participants with a history of falling or balance problems. Onward referral to 'active' intervention will be based on falls risk determined from balance screen. The primary outcome is peripheral fracture; secondary outcomes include number with at least one fracture, falls, mortality, quality of life and health service resource use at 18 months, captured using self-report and routine healthcare activity data. Ethics and dissemination: The study protocol has approval from the National Research Ethics Service (REC reference 10/H0401/36; Protocol V.3.1, 21/May/2013). User groups and patient representatives were consulted to inform trial design. Results will be reported at conferences and in peer-reviewed publications. A patient-friendly summary of trial findings will be published on the prevention of falls injury trial (PreFIT) website. This protocol adheres to the recommended SPIRIT Checklist. Amendments will be reported to relevant regulatory parties. Trial registration number: ISRCTN 71002650; Pre-results.